"E travesti trabalha?": divisão transexual do trabalho e messianismo patronal - Joao Felipe Zini Cavalcante de Oliveira (2019)
Transvestites and transsexuals have traditionally been left out of society becauseof the stigma attached to them. Most of them end up being inserted inprostitution, either by choice or necessity, and have their insertion in the formallabor market spoiled by prejudice and discrimination. To these people (whosehumanity is even questioned by imposed standards) society instantly attributesprostitution and HIV, but they are definitely not limited to that. Transvestiteworks, and works under conditions that tend to further exploit their labor force.Because of the prejudice that already relates them to conditions of marginality,there is a greater tendency of their employers to attribute themselves the"virtue" of saviors and thus would be in a position to "demand more" becauseof the "opportunity" offered by them. This work seeks to understand the laborreality of transvestites and transsexuals when they are inserted in the formal jobmarket, but also the conditions that permeate it, which precede it and, perhaps,those that follow. We will go through a reconstruction and designation ofimportant concepts to understand the phenomenon studied; the life stories oftransvestites and transsexuals interviewed throughout the research, until it reaches a point where it will be possible to analyze how the transvestite - employer relationship occurs and to perform a critique of employment as "salvation".